2014
DOI: 10.1093/ejcts/ezu472
|View full text |Cite
|
Sign up to set email alerts
|

Da Silva's cone repair for Ebstein's anomaly: effect on right ventricular size and function

Abstract: Da Silva's cone repair for Ebstein's anomaly creates excellent valve function in all patients. Consecutively, the size of the RV decreases and the antegrade net stroke volume increases 6 months after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 21 publications
3
29
0
1
Order By: Relevance
“…As in our work, prior studies have found that the cone operation leads to a decrease in RV EDV [ 6 , 12 14 ]. The effect on RV EF is less consistent with some investigations showing no change [ 6 , 12 ] as we found, and others showing a decrease [ 13 , 14 ]. This discrepancy may reflect variations among the studies in the indications for surgery and timing of the postoperative evaluation, and requires further study.…”
Section: Discussionsupporting
confidence: 79%
“…As in our work, prior studies have found that the cone operation leads to a decrease in RV EDV [ 6 , 12 14 ]. The effect on RV EF is less consistent with some investigations showing no change [ 6 , 12 ] as we found, and others showing a decrease [ 13 , 14 ]. This discrepancy may reflect variations among the studies in the indications for surgery and timing of the postoperative evaluation, and requires further study.…”
Section: Discussionsupporting
confidence: 79%
“…Today, if surgery is indicated, most patients with Ebstein's anomaly are managed with a cone operation 3 at our centre with very good results. 4 However, in patients in whom tricuspid valve reconstruction results in unacceptable haemodynamics, a cavo-pulmonary shunt, hence a so-called 1 ½ circulation, may be helpful as it was in our patient. 2,5,6 Severe intrapulmonary shunts with subsequent increasing arterial cyanosis are a known long-term complication after a classical Glenn operation or a Kawashima procedure, where the hepatic blood does not reach parts of the pulmonary arteries.…”
Section: K Gendera Et Almentioning
confidence: 65%
“…In recent years, many authors have published successful management of Ebstein's anomaly using biventricular approaches [19-21] . In our series, the residual RV after plication of ARV was 70% of the expected indexed RV volume, which precludes a biventricular repair.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the residual RV after plication of ARV was 70% of the expected indexed RV volume, which precludes a biventricular repair. Lange et al [21] have not added a BCPS to their repair, probably because of a different subset of patients in their series, as their postoperative RV end diastolic volume was close to normal. However, they left an interatrial communication of 5-6 mm in their patients, which would act as a trigger to decompress a failing RV.…”
Section: Discussionmentioning
confidence: 99%